2020
DOI: 10.1186/s12986-019-0420-1
|View full text |Cite
|
Sign up to set email alerts
|

Insoluble dietary fibre intake is associated with lower prevalence of newly-diagnosed non-alcoholic fatty liver disease in Chinese men: a large population-based cross-sectional study

Abstract: Background: The health benefits of dietary fibre (DF) intake on non-alcoholic fatty liver disease (NAFLD) are controversial. Thus, this large cross-sectional study aimed to determine the associations between DF intake and the prevalence of newly-diagnosed NAFLD in a large general population. Methods: A total of 23,529 participants were enrolled in the analyses. Newly-diagnosed NAFLD was diagnosed according to liver ultrasonography and history of alcohol intake. DF intake was assessed using a validated selfadmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 34 publications
1
22
1
3
Order By: Relevance
“…Comparative nutritional evaluation studies suggested that patients with NAFLD consumed less dietary fiber than healthy individuals [95,96]. In comparison, the consumption of dietary fiber has been a favorable factor resistant to the progression of NAFLD [97]. Fibers leaving the upper gastrointestinal tract are degraded into SCFAs including acetate, butyrate, and propionate through the fermentation of gut microbiota at the lower part of the gastrointestinal tract [98].…”
Section: Dietary Fibersmentioning
confidence: 99%
“…Comparative nutritional evaluation studies suggested that patients with NAFLD consumed less dietary fiber than healthy individuals [95,96]. In comparison, the consumption of dietary fiber has been a favorable factor resistant to the progression of NAFLD [97]. Fibers leaving the upper gastrointestinal tract are degraded into SCFAs including acetate, butyrate, and propionate through the fermentation of gut microbiota at the lower part of the gastrointestinal tract [98].…”
Section: Dietary Fibersmentioning
confidence: 99%
“…To date, clinical data from such studies are disputed, but most of them report loss of body weight, suggesting that probiotic supplementation can be used as a complementary approach for patients with NAFLD [163]. Furthermore, high intake of insoluble dietary fiber correlates with a lower prevalence of NAFLD [164], and high-fiber diets promote short-chain fatty acid producing microbiota with beneficial effects in T2DM patients [165]. Clinical data on such diets in NAFLD patients are currently lacking.…”
Section: Dietary Interventionsmentioning
confidence: 99%
“…Other cross-sectional studies with 1639 participants reported that the intake of whole grains could lower the risk of NAFLD (OR: 0.72; 95%CI: 0.61, 0.98) [43]. Besides, a larger cross-sectional study based on 23,529 participants showed that the consumption of insoluble dietary fiber (a type of nonstarch polysaccharide widely found in whole grains) was inversely associated with the risk of NAFLD (OR: 0.7; 95%CI: 0.61, 0.85) [44]. However, controversial results still existed among different studies.…”
Section: Epidemiological Evidence On the Relation Between Plant-basedmentioning
confidence: 99%